2002
DOI: 10.1046/j.1365-2249.2002.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chromium and copper supplementation on mitogen-stimulated T cell proliferation in hypercholesterolaemic postmenopausal women

Abstract: SUMMARYThe purpose of this study was to analyse effects of chromium and/or copper supplementation on immune function in hypercholesterolaemic postmenopausal women. A 2 Â 2 factorial research design was used and 40 subjects were supplemented with 0´394 g lactose, 200 mg Cr, 3´0 mg Cu, or 200 mg Cr and 3´0 mg Cu/d for 12 weeks. A significant interactive effect of Cr and Cu supplementation on lymphocyte proliferation was observed with ConA 50 mg/ml stimulation. After 12 weeks of supplementation, ConA-stimulated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Another study demonstrated a copper requirement for the oligomerization of chemokines for inducing T‐cell migration (43). Lastly, lymphocytes collected from patients who had received 12 wk of Cu + and Cr + supplements showed decreased proliferation in response to in vitro stimulation compared to those from patients who had only received Cr + supplementation over that time period (44). The fact that we did not observe a defect in IL‐2 production associated with concentrations of Dp44mT necessary to inhibit T‐cell activation suggests that copper may simply mediate the drug's activity in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated a copper requirement for the oligomerization of chemokines for inducing T‐cell migration (43). Lastly, lymphocytes collected from patients who had received 12 wk of Cu + and Cr + supplements showed decreased proliferation in response to in vitro stimulation compared to those from patients who had only received Cr + supplementation over that time period (44). The fact that we did not observe a defect in IL‐2 production associated with concentrations of Dp44mT necessary to inhibit T‐cell activation suggests that copper may simply mediate the drug's activity in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Cr (III) does not only have roles in innate immune system but also in humoral one. Lymphocytic proliferation was found to decrease when copper was added to Cr supplementation in Rhee et al study (Rhee et al 2002 ). Another study found that antibody production decreased, spleen weight lessened, splenocytes number and percentage of blood lymphocytes were reduced in Oreochromis mossambicus fish when exposed to either trivalent or hexavalent Cr (Arunkumar et al 2000 ).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that supplementation with Vitamin E, a potent antioxidant, and trace elements, such as Zinc (Zn), Selenium (Se), and Copper (Cu), improves the immune response. For example, Vitamin E increases lymphocyte proliferation in response to mitogens 25 ; Zn enhances phagocytic activity and antigen presentation to T-lymphocytes 26,27 ; Se and Cu increase T-cell differentiation and proliferative responses, superoxide dismutase, and IL-2 levels [28][29][30][31][32] . In view of these beneficial effects, it is relevant to evaluate the effect of such supplements to improve the immune system function after SCI.…”
Section: Introductionmentioning
confidence: 99%